Investigation of the dynamic behaviors of the nonlinear operators generated from Î¾ (as)-QSO - Garalleh, Hamzah; Termimi Ab Ghani, Ahmad; Qaralleh, I. (International Journal of Engineering and Technology, 2018)
A quadratic stochastic operator (QSO) exhibits the time development of various species in biology. Several QSOs have been examined by Lotka and Volterra. The main problem in a nonlinear operators is to explore their behavior. The behavior of a nonlinear operators have not been studied in comprehensively even QSOs which are the simplest a nonlinear operators. To address this problem, many classes of QSO were introduced. This paper aims to examine the behavior of six an operators selected from different classes of Î¾ (as)-QSO.